Perception of health sciences students about their training in health promotion - Santos-Falcón, Gladys (2009)
Objectives: To identify a Peruvian Faculty of Medicine students’ perception on training in health promotion. Design: Quantitative-qualitative study. Institution: Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Participants: Faculty of Medicine’s five academic professional schools penultimate year students. Interventions: Two data collection techniques -an interview with a modified Lickert questionnaire and focus group- were applied to 127 students. Main outcome measures: Quantification of the students’ perception on their training on health promotion strategies in relation to Ottawa’s Letter proposition on health promotion. Results: The students’ perception on their health promotion strategies training was moderately favorable, with tendency to be quite favorable in two them: School of Nursing in creating supportive environments for health and strengthening community action, with 70,5% and 59,3% respectively; School of Nutrition students had a completely favorable perception on implementing public policies, in 60,9%. It should be noted that only in one dimension (personal abilities) the students’ perceptions was unfavorable in two schools: Medical School, in 23,4%, and Medical Technology, in 20,4%. With the qualitative data we structured seven analysis categories: 1) appreciating health promotion; 2) linking health promotion with community care; 3) being motivated to promote health; 4) appreciating community strengthening; 5) determining the Faculty should promote health; 6) considering factors that hinder health promotion; and, 7) appreciating interdisciplinary involvement in health promotion. Conclusions: The Faculty of Medicine students had varied perception in relation to health promotion formation, according to strategies proposed by Ottawa’s Letter. It will be necessary to unify and improve training in order to develop interdisciplinary health and confront health complex problems present in our society.